(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
This study aimed to evaluate effect of Gum Arabic powder level (GAL) as a bio-edible coating and drying periods on quality and rehydration properties of dry camel meat. Camel meat was trimmed of fat, prepared into thin strips of 1x1x10 cm, and divided into three equal groups. The groups were GAL0%, GAL5% and GAL10% coated with 0% (control), 5% or 10%Gum Arabic powder. Each group was divided into 3 sub-groups and subjected to three drying periods (DP) 0 hours (fresh), 48 or 96 hours. After drying to the specified period, water activity, pH, peroxide value, total bacterial count (cfu/g), rehydration capacity and sensory evaluations were determined for each treatment. The results revealed a significant interaction between the GAL and the DP in the water activity, total bacterial count (cfu/g) and odor scores. Increasing both GAL and DP resulted in a significant increase in the odor scores and significant decrease in water activity and total bacterial count (cfu/g). Increasing the GAL resulted in a significant increase in sensory scores, pH, peroxide value, and total bacterial count. The GAL10% dried for 96hrs had the highest odor scores (4.8). The rehydration percentage in boiled water (100⁰C) was significantly lower than that in tab water. The rehydration of dry meat inform of powder was about 3 times higher than that of strip form in all treatments. It can be concluded that the Gum Arabic powder as natural edible coating for dehydrated camel meat improved its appearance, odor and color. Water temperature and physical from of dried meat (strip or powder) can affect the rehydration ability of dried camel meat